A Study on Public Perception Towards Digital Billboard Advertisements With Special Reference to Tirupur City - Karpagavalli, V.; Kaaviya, K. (Indian Journal of Computer Science, 2025)
This study aims to examine the attitudes and opinions of residents in Tirupur towards digital billboard advertisements. This research seeks to explore how individuals observe and interact with outdoor advertising in rapidly developing urban surroundings. The study will analyze factors such as the effectiveness of digital billboards, their impact on consumer behavior, and the overall response of these advertisements among the public. Through surveys, interviews, and observational research, the study intends to get together valuable insights into the preferences, attitudes, and responses of residents towards digital billboard advertisements in Tirupur. By accepting the public perception of outdoor advertising, advertisers and marketers can alter their strategies to better engage with the local community and improve the effectiveness of their campaigns. The findings of this study can be used to provide valuable information to advertisers, marketers, and city planners to optimize the use of digital billboard advertisements in Tirupur. Ultimately, this research aims to contribute to a deeper understanding of the role of outdoor advertising in influencing consumer buying behaviour and shaping public perceptions in urban settings like Tirupur.